Multicenter research in dialysis centers in Brazil: recruitment and implementation of the SARC-HD study - Duarte, Marvery P.; Nóbrega, Otávio T.; Vogt, Barbara P.; Vieira, Fábio A.; Mondini, Dário R.; Silva, Maryanne Z.C. [UNESP]; Disessa, Henrique S. [UNESP]; Krug, Rodrigo R.; Sant'Helena, Bruna R.M.; Bundchen, Daiana C.; Bohlke, Maristela; Adamoli, Angélica N.; et al. (FapUNIFESP (SciELO), 2025)
Introduction: Multicenter research initiatives in Brazilian dialysis centers are scarce. We described the recruitment and implementation phases of the SARC-HD study, aimed at investigating sarcopenia and its impact on adverse clinical outcomes. Methods: The SARC-HD is a cohort study being conducted with patients on hemodialysis in Brazil. The recruitment phase was defined as the period from the invitation to the center until the start of patient enrollment, whereas the implementation phase lasted from then until the completion of enrollment and baseline data collection. Upon implementation, a structured questionnaire was distributed to collect feedback from principal investigators. Results: 21 centers from three Brazilian regions consented to participate, with two dropping out. Ten principal investigators oversaw the 19 sites. Nine centers (47%) were funded entirely by health insurance companies. A total of 1525 patients were screened for eligibility and 1008 were enrolled, with a 66.1% recruitment rate. Recruitment and baseline data collection took 12 [interquartile range: 5-15] weeks. Qualitative content analysis identified barriers such as a lack of infrastructure and logistics for research. Facilitators included the management and organization of the steering committee. Data collection challenges were mainly reported with the subjective 7-point global assessment and the international physical activity questionnaire. The main challenge for the ongoing maintenance phase will be the lack of standardized information in electronic health records. Conclusions: The recruitment and implementation phases of the multicenter SARC-HD study were feasible. Barriers and facilitators identified by principal investigators may help future multicenter initiatives to integrate research-related tasks into clinical routine, facilitating successful experiences.
Pesquisa multicêntrica em centros de diálise no Brazil: recrutamento e implementação do estudo SARC-HD
Keywords: Chronic Kidney Disease; Data Collection; Health Information Management; Hemodialysis; Sarcopenia